Simplified approach to evaluate displacement of laced steel-concrete composite beams for blast loads - Thirumalaiselvi, A.; Anandavalli, N.; Rajasankar, J.; Iyer, Nagesh R. (Journal of Structural Engineering, 2025)
Laced Steel-Concrete Composite (LSCC) system consists of perforated steel cover plates, which are connected using reinforcing members and cross rods, and in filled with concrete. Experimentally, it has been demonstrated that LSCC beam possess high rotational capacity, which makes it suitable to resist suddenly applied loads such as due to blast. In this paper, LSCC beams with varying cover plate thickness subjected to blast loads have been analyzed using two different techniques: (i) an equivalent single degree of freedom (SDOF) model using Duhamel’s integral and Newmark-beta method and (ii) multiple degree of freedom (MDOF) model using finite element analysis. LSCC beam is idealized as simply supported beam using equivalent steel beam approach. Triangular blast pressure distribution is adopted in the study. Finite element model of LSCC beam is generated using a combination of solid, shell and beam elements.Comparison of fundamental frequency values obtained by SDOF and MDOF analysis indicates that the idealization of the beam as SDOF system results in a stiffer system. Maximum displacement obtained using SDOF system is found to be less than that obtained using MDOF system.